Is Online Learning Accessible During COVID-19 Pandemic? Voices and Experiences of UIN Sunan Kalijaga Students with Disabilities - Ro'fah, Ro'fah; Hanjarwati, Astri; Suprihatiningrum, Jamil (FITK UIN Walisongo, 2020)
The study seeks to examine the voices and experiences of students with disabilities in navigating online learning during the COVID-19. Based on in-depth interviews with thirty-four students with various disabilities of UIN Sunan Kalijaga, this study attempts to answer how these students experiencing online learning, what challenges they encounter, and what strategies they are using to navigate this new way of learning. Results show most students prefer conventional face-to-face learning, compared to the online learning one. Students reported various challenges they experienced, the most important of which is the high cost of internet access. Other challenges include the inaccessibility of the e-learning system with respect to the platform of online learning and the learning activities. Students also concerned with the absence of supports that they normally received from the university’s disability office (Pusat Layanan Difabel/ PLD). These challenges have encouraged students to seek help from family members, peers, and lecturers.Abstrak Studi ini berupaya untuk mengevaluasi pendapat dan pengalaman siswa penyandang cacat dalam menavigasi pembelajaran online selama COVID-19. Berdasarkan wawancara mendalam dengan tigapuluh empat mahasiswa dengan berbagai kecacatan di UIN Sunan Kalijaga, penelitian ini mencoba menjawab bagaimana para siswa ini mengalami pembelajaran online, tantangan apa yang mereka hadapi, dan strategi apa yang mereka gunakan untuk menavigasi cara belajar baru ini. Hasil menunjukkan sebagian besar siswa lebih suka pembelajaran tatap muka konvensional, dibandingkan dengan pembelajaran online. Siswa melaporkan berbagai tantangan yang mereka alami, yang terpenting adalah tingginya biaya akses internet. Tantangan lain termasuk tidak dapat diaksesnya sistem e-learning sehubungan dengan platform pembelajaran online dan kegiatan pembelajaran. Siswa juga khawatir dengan tidak adanya dukungan yang biasanya mereka terima dari Pusat Layanan Difabel (PLD) universitas. Tantangan-tantangan ini telah mendorong siswa untuk mencari bantuan dari anggota keluarga, teman sebaya, dan dosen